The Role of Radiopathological Evaluation in Diagnosis of Beckwith-Wiedemann Syndrome - Gangadhar, Kiran; Santhosh, D; Maurya, I (Nepalese Journal of Radiology, 2013)
Beckwith-Wiedemann Syndrome (BWS), an overgrowth syndrome is associated with early development of embryonal tumours usually in the first four years of life. Hepatoblastoma is observed in 1% to 3% of persons with Beckwith-Wiedemann Syndrome or isolated hemihypertrophy(HH). We report a case of hepatoblastoma associated with both BWS and HH with raised serum alpha-feto protein levels and hypoglycaemia. Nepalese Journal of Radiology; Vol. 2; Issue 2; July-Dec. 2012; 86-91 DOI: http://dx.doi.org/10.3126/njr.v2i2.7693